THE METHODOLOGY FOR CALCULATING OF LABOR COSTS OF MEDICAL PERSONNEL IN MARKET CONDITIONS - S. V. Katasonov; P. S. Kyzlasov (Исследования и практика в медицине)
The article presents the approximate calculations of working time of physician to work with the patient and documentation. On the base of these calculations they outline the possible ways to optimize the work of the medical staff.